2010
DOI: 10.1007/s00405-010-1419-4
|View full text |Cite
|
Sign up to set email alerts
|

Complications of hyoid suspension in the treatment of obstructive sleep apnea syndrome

Abstract: The objectives of the study are to assess adverse events and complications of hyoid suspension (HS) as a treatment of obstructive sleep apnea syndrome (OSAS). The study design was cohort. Thirty-nine patients with OSAS and obstruction at tongue base level, as assessed by sleep endoscopy, underwent HS. Information about adverse events and complications were obtained by reviewing charts and patient-completed questionnaires. The mean follow-up period from surgery to last control visit was 13.1 months (range 2-38)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Despite the increasing number of reports about hyoidthyroidpexia, there is still insufficient evidence to recommend one suspension technique over another [23]. Nevertheless, as far as we could experience and in accordance with the literature, hyoidthyroidpexia has been shown to be a safe procedure without any major complications [24]. …”
Section: Discussionmentioning
confidence: 85%
“…Despite the increasing number of reports about hyoidthyroidpexia, there is still insufficient evidence to recommend one suspension technique over another [23]. Nevertheless, as far as we could experience and in accordance with the literature, hyoidthyroidpexia has been shown to be a safe procedure without any major complications [24]. …”
Section: Discussionmentioning
confidence: 85%
“…1,2 Surgical treatment of OSA includes the hyoid suspension procedure, which has relatively few complications. 3,4 Infection unresponsive to antibiotics can occur after thyrohyoid or hyomandibular suspension, 3 HO has not been reported after hyoid suspension; however, HO in the head and neck has been described in the trachea post-tracheostomy in a mechanically ventilated patient 5 and in the setting of stylohyoid ossification (Eagle's Syndrome). HO can occur in soft tissues without obligate proximity of bony structures, although in this case, typical for traumatic HO, proximity to bone supports the seeding theory regarding bone formation.…”
Section: Discussionmentioning
confidence: 97%
“…1,2 Surgical treatment of OSA includes the hyoid suspension procedure, which has relatively few complications. 3,4 Infection unresponsive to antibiotics can occur after thyrohyoid or hyomandibular suspension, 3 generally considered due to foreign body infection (personal communication with Dr Nico de Vries, May 2006), potentially explaining the partial erosion of the central hyoid bone underlying the suture material.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, no infection had been observed. Richard et al [32] , reported a deviated tongue in one patient for a short period, which resolved within a few postoperative weeks, a wound abscess reported in another case and fistula in two patients, who needed more surgical interventions. Hou et al [33] , two patients had perioperative tongue swelling.…”
Section: Disucssionmentioning
confidence: 94%